Rapa’i Sebagai Inspirasi Penciptaan Karya Kriya Seni - Hamzah, M (Pascasarjana Institut Seni Indonesia Padang Panjang, 2023)
Rapa 'i is a traditional membrane day instrument that exists to this day. As rapa 'i progressed, events in the past inspired the creation of kriya's art. One of these phenomena is that most of the people today do not know that rapa 'i is the present medium because of the islamiah and as a medium for the past, so that no doubt of rapa 'i can be, as well as whether rapa 'i is being played on the holy moon of maulid the prophet. The phenomenon felt by researchers is an inspiration for the creation of art with the concept of symbolic expression. Applying the symbolic expression concept to moda disformation and stilisation. Applied moda disformation in rapa 'i's circular baloeh (frame), suncave and line ornaments. Moda stilisation applied isa ornamentation of calligraphic motif in the field of work. This method of creation by means of various stages, including the stages of exploration, experiment, reflection and formation. The basic materials used in this work are surian wood and tissue paper. The selection of a wooden medium used had an elevating density. The technique used in the creation of the work is the bevel of section 20 and engraving. Tenik finishing used was laminating techniques and deep-texture techniques